2014
DOI: 10.2134/jeq2013.12.0530
|View full text |Cite
|
Sign up to set email alerts
|

Grazing and No-Till Cropping Impacts on Nitrogen Retention in Dryland Agroecosystems

Abstract: As the world's population increases, marginal lands such as drylands are likely to become more important for food production. One proven strategy for improving crop production in drylands involves shifting from conventional tillage to no-till to increase water use efficiency, especially when this shift is coupled with more intensive crop rotations. Practices such as notill that reduce soil disturbance and increase crop residues may promote C and N storage in soil organic matter, thus promoting N retention and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 42 publications
(49 reference statements)
0
1
0
Order By: Relevance
“…For example, a meta-analysis by Tonitto et al (2006) found legume and non-legume cover crops both reduced nitrate leaching amounts compared to fallow, by 40 and 70%, respectively. In semiarid regions, perennial grass ecosystems have been found to retain[90% of added N in the long term (15 years) compared to only 30% in annually cropped ecosystems (Mobley et al 2014).…”
Section: Nitrate Leaching Resultsmentioning
confidence: 99%
“…For example, a meta-analysis by Tonitto et al (2006) found legume and non-legume cover crops both reduced nitrate leaching amounts compared to fallow, by 40 and 70%, respectively. In semiarid regions, perennial grass ecosystems have been found to retain[90% of added N in the long term (15 years) compared to only 30% in annually cropped ecosystems (Mobley et al 2014).…”
Section: Nitrate Leaching Resultsmentioning
confidence: 99%